FIRST ERASMUS MUNDUS MASTER COURSE IN NURSING - Maria Pilar Mosteiro Díaz (Revista de Pesquisa Cuidado é Fundamental Online)
In 2010 and within the European Call for Erasmus Mundus proposals, the University of Oviedo together with three partner institutions, the University of Metropolia Helsinki (Finland), the University of the Algarve and the Polytechnic Institute of Santarém (both in Portugal), submitted a first-time proposal for a Masters Degree in Nursing. The quality, originality and soundness of the project enabled its selection out of 171 applications from different universities and degrees.